Roots, Cycles and Leaves. Expression of the Phosphoenolpyruvate Carboxylase Kinase Gene Family in Soybean - Sullivan, Stuart (American Society of Plant Biologists, 2004)
Phosphorylation of phosphoenolpyruvate carboxylase (PEPc; EC 4.1.1.31) plays an important role in the control of central metabolism of higher plants. This phosphorylation is controlled largely at the level of expression of PEPc kinase (PPCK) genes. We have analyzed the expression of both PPCK genes and the PEPC genes that encode PEPc in soybean (Glycine max). Soybean contains at least four PPCK genes. We report the genomic and cDNA sequences of these genes and demonstrate the function of the gene products by in vitro expression and enzyme assays. For two of these genes, GmPPCK2 and GmPPCK3, transcript abundance is highest in nodules and is markedly influenced by supply of photosynthate from the shoots. One gene, GmPPCK4, is under robust circadian control in leaves but not in roots. Its transcript abundance peaks in the latter stages of subjective day, and its promoter contains a sequence very similar to the evening element found in Arabidopsis genes expressed at this time. We report the expression patterns of five PEPC genes, including one encoding a bacterial-type PEPc lacking the phosphorylation site of the plant-type PEPcs. The PEPc expression patterns do not match those of any of the PPCK genes, arguing against the existence of specific PEPc-PPCK expression partners. The PEPC and PPCK gene families in soybean are significantly more complex than previously understood.